2000
DOI: 10.1016/s0735-1097(00)00815-9
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative exercise tolerance after aortic valve replacement by small-size prosthesis

Abstract: Valve replacement by small aortic prosthesis does not seem to be a factor of exercise intolerance as assessed by VO2max in patients without LVEF dysfunction before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is possible that the decrease in peakVO 2 in our patients was, at least in part, attributable to a more sedentary lifestyle postoperatively. Becassis et al (2000) found no significant difference in peakVO 2 between a group of healthy controls and patients who had received aortic heart valve prosthesis 1 year postoperatively. This could indicate that the heart valve or the open heart surgery per se did not affect peakVO 2 .…”
Section: Discussionmentioning
confidence: 69%
“…It is possible that the decrease in peakVO 2 in our patients was, at least in part, attributable to a more sedentary lifestyle postoperatively. Becassis et al (2000) found no significant difference in peakVO 2 between a group of healthy controls and patients who had received aortic heart valve prosthesis 1 year postoperatively. This could indicate that the heart valve or the open heart surgery per se did not affect peakVO 2 .…”
Section: Discussionmentioning
confidence: 69%
“…A recent publication by Becassis et al [29] reported that, even though there was no difference in exercise tolerance, mean and peak transprosthetic pressure gradients significantly increase during exercise, and thus the difference may be exaggerated during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…These effects balance those of mitral regurgitation jet on the left atrial pressure which is normal in compensated patients. Although the atrial size is increased in mitral regurgitation, the risk of thrombus formation is much less than that seen in mitral stenosis because of the fast regurgitant jet that speeds the atrial blood circulation [35].…”
Section: Pathophysiology Of Mitral Regurgitationmentioning
confidence: 99%
“…Rarely, if transthoracic and, when needed, transesophageal echocardiography or cinefluoroscopy studies are not informative in a patient with exertional symptoms, exercise stress echocardiography may be needed to assess the valve prosthesis function at higher cardiac output [28]. A disproportionate (>100%) rise of transvalvular gradient suggests prosthesis dysfunction [29][30][31][32][33][34][35][36]. Despite its use in determining efficient valve function, most studies do not show a convincing correlation between valve size, resting and exercise gradients and exercise tolerance [34][35][36].…”
Section: Valve Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation